Poverty and inequality in access to sexual and reproductive health care for Peruvian women - Pacovilca-Alejo, Gelber Sebasti (2024)
Objective: To determine the influence of poverty on sociogeographic inequalityin the access to sexual and reproductive health of Peruvian women. Methods: Anobservational, analytical and ecological study with aggregate data corresponding toMetropolitan Lima, Constitutional Province of Callao and 24 departments of Peruregistered for the year 2021 by the National Institute of Statistics and Informaticsof Peru. The analysis included correlation tests, simple linear regression and thecalculation of Kuznets indices, inequality concentration index (ICI) and slope inequalityindex (SII). Results: The proportion of women not using modern contraceptivemethods was associated with the proportion of population in monetary poverty(r=0.448; p=0.022) with an absolute inequality gap of 6.92% and relative inequalitygap of 1.16 (ICI =0.034; SII=7.875). The proportion of pregnant women withoutprenatal care by qualified health personnel and the proportion of deliveries withoutassistance from skilled health workers were associated with the proportion of thepopulation in nonmonetary poverty. The absolute and relative inequality gapswere 5.29% and 8.90 (ICI=0.526; SII=5.270) for prenatal care, and 11.33% and 11.03(ICI=0.453; SII=12,440) for delivery care. Conclusions: Non-monetary poverty wouldexplain the inequality gaps observed in the proportion of pregnant women withoutprenatal care by qualified health personnel and the proportion of deliveries withoutthe assistance of skilled health personnel in Peruvian women.